2003
DOI: 10.2320/matertrans.44.118
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of an Exponential Law in Creep of Metals

Abstract: An exponential type creep equation has been developed for heat resistant steels by the authors. This equation was induced assuming both a thermally activated process for a mobile dislocation and rather high applied stress. The applicability of the new creep equation was examined for a pure iron, two kinds of Ni-base super alloys and an eutectic solder alloy in a Pb-Sn system which were tested at relatively high temperatures and under very low stresses. All of the data obtained were completely explained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…[1] was confirmed for rupture data of many kinds of heat-resistant steels and alloys. [17,18] Further, the activation volume is defined as the product of the area swept by dislocations and the length of the Burgers vector when we discuss the microscopic deformation mechanisms by dislocations. However, since it is impossible to measure directly the area swept by dislocations, another interpretation is necessary from a creep-deformation-measuring point of view.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] was confirmed for rupture data of many kinds of heat-resistant steels and alloys. [17,18] Further, the activation volume is defined as the product of the area swept by dislocations and the length of the Burgers vector when we discuss the microscopic deformation mechanisms by dislocations. However, since it is impossible to measure directly the area swept by dislocations, another interpretation is necessary from a creep-deformation-measuring point of view.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…I and III¢ as shown in Figure 8. The values of Q for time to rupture of many kinds of heat-resistant steels do not exceed 500 kJ/mol, [16][17][18] although Q increases to some extent at high temperatures in some cases. [16] In a high-temperature region higher than 973 K (700°C), neither Laves phase nor Z phase precipitates in high-Cr martensitic steel containing Mo and/or W, [25,29] and therefore, major strengthening factors are considered to be both W and/or Mo, most of which are soluble, and fine MX particles that precipitate stably in the martensitic matrix.…”
Section: A Creep Mechanisms For Grs I-iii¢mentioning
confidence: 96%
“…In recent studies on creep mechanisms, the exponential type equation has been applied to many heat resistant steels by Tamura et al [13][14][15][16]. It is shown that this application is available for summarizing and discussing creep properties.…”
Section: Exponential Type Creep Constitutive Equationmentioning
confidence: 99%
“…However, recently availability of a following exponential equation for fitting t r has been re-confirmed. 26,27) …”
Section: Analysis Of Creep Curves Of F82hdmentioning
confidence: 99%